SUDDEN FAILURE OF POSTURE CONTROL IN ELDERLY: THE AID PRACTICE IN AN INVESTIGATION APPROACH - Maria Helena Lenardt; Maria Terumi Maruyama Kami; Cristiane Brey (Universidade Federal do Paraná, 2001)
This study is a research exploratory descriptive, of wich the purpose is develop an education approach for the practice of nursing's cares in emergence service of the failure in elderly of control posture, in Emergence's Service, identifing, bringuing up these cause and guiding the elderly attended and their family in relation toward the prevention of the problem. The study was 0developed in an emergence service of a Universty Hospital, extending to the aisle of admission of the Ortophedic Clinic, in Curitiba city. The population of this study was formed by elderly (equals or above 60 years old) of both sex, wich entered inside in the trainee ship's field, during the taisen period between the months of september and october of 2000,who have suffered of falls accident, with a total of 39 elderly. The recognition of the research were: the predominating of female sex (66, 67%); the incidente in family environment (82,05%); on their own accidents falls (61,54%); the slippery floor as the principal mean of the fall (29,03%); and the femur's fracture (55%) as hartm of greater incidence. The result of analysis, conclud that fall's accident form a great problem to people at this age. Theeducativa approach, focusing the prevention of falls for external factors, during the care's practice, it is necessary and it is an important instrument for the attempt of reducing the frequency of this accident.